Поняття та форми капітального будівництва в Україні - Олюха, Віталій Георгійович; Олюха, Виталий Георгиевич; Oljuha, Vitalij (My University, 2013)
The article investigates the features that allow to allocate a category «capital construction». It was proved the expediency of its preservation and future use. Also it was considered forms of capital construction. Was substantiated the expediency of their use in public-private partnership.
Олюха В. Г. Поняття та форми капітального будівництва в Україні / В. Г. Олюха // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 499-507.
Keywords: капітальне будівництво; форми капітального будівництва; державно-приватне партнерство; капитальное строительство; формы капитального строительства; государственно-частное партнерство; capital construction; forms of capital construction; public-private partnership